A Novel Of Dual-Band Bandpass Filter Employing Coupled Stepped Impedance Resonator And U-Shaped Defected Microstrip Structure (DMS) - Masrukin, Yully Erwanti; Zakaria, Zahriladha; Sam, Weng Yik; Sadick Ali, Nur Shaheera Alia (Praise Worthy Prize, 2017)
This paper presents the integration between a pair of coupled asymmetric stepped impedance resonators (SIRs) and U-shaped Defected Microstrip Structure (DMS) in producing of dual-band bandpass filter (BPF). In this study, as the DMS were integrated with SIR bandpass filter, the low loss, high attenuation and good selectivity between dual-bandpass were produced. The DMS was designed at resonant frequency of 3 GHz with the attenuation is better than 60 dB. The measured results show two bandpasses centered at 2.50 GHz and 3.50 GHz with the fractional bandwidth of 16% and 18.3%, respectively. Meanwhile, the return and insertion losses are greater than 15dB and 1dB, respectively. Additionally, the proposed filter is designed with 3 transmission zeroes with the attenuation level more than 50dB. The simulated and measured results are both presented and show a good agreement. This filter is very useful in modern wireless communication and many applications.